CULTURA Y ECOTURISMO COMO ESTRATEGIAS DE TRANSFORMACIÓN URBANA PARA PUERTO LÓPEZ META (2021)
Puerto López Meta is recognized nationally as the "geographic center of Colombia." For many years it has been cataloged as being the faithful representative of its culture, tourism and sports, those great virtues of the municipality are developed through its day to day and also through festivities; which are important since they are part of the cultural heritage and that thanks to this Puerto López becomes known as an importa tourist, cultural and sports aspects.